2010
DOI: 10.1631/jzus.b1000012
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between serum lipid, lipoprotein, triglyceride-rich lipoprotein, and high-density lipoprotein particle concentrations in post-renal transplant patients

Abstract: Abstract:Objective: Disturbances in lipid and lipoprotein profiles in patients after kidney transplantation (Tx) are still not understood. Methods: Serum levels of lipids, lipoprotein, triglyceride-rich lipoproteins (TRLs), and high-density lipoprotein (HDL) particles were determined, lipid and lipoprotein ratios were calculated, and their relationships in Tx patients with hypertriglyceridemia (HTG) and lower apolipoprotein AI (apoAI) concentration were examined. Serum lipid and lipoprotein levels were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Studies have shown a role of parathyroidectomy in reducing triglyceride levels in CKD patients [26,27] . Among renal transplant recipients, it has been seen that lipids and lipoprotein profile ratios were more beneficial when the TG levels were less than 150 mg/dL and apoA1 was greater than 150 mg/dL when compared to the opposite [28] . They are also on immunosuppressive medications, many of which affect the lipid profile adversely.…”
Section: Lipid Profile In Kidney Diseasesmentioning
confidence: 99%
“…Studies have shown a role of parathyroidectomy in reducing triglyceride levels in CKD patients [26,27] . Among renal transplant recipients, it has been seen that lipids and lipoprotein profile ratios were more beneficial when the TG levels were less than 150 mg/dL and apoA1 was greater than 150 mg/dL when compared to the opposite [28] . They are also on immunosuppressive medications, many of which affect the lipid profile adversely.…”
Section: Lipid Profile In Kidney Diseasesmentioning
confidence: 99%
“…No cardiac incidence occurred in Tx patients. The control group consisted of 89 subjects chosen from among apparently normolipidemic people as described previously (Kimak et al, 2010). The study was carried out in accordance with the guidelines of the Ethics Committee of the Medical University of Lublin, Poland.…”
Section: Participantsmentioning
confidence: 99%
“…Serum was immediately separated and stored in aliquots at −80 °C until use. Routine laboratory parameters (the levels of urea, uric acid, creatinine, total protein, and albumin) and lipids and lipoproteins (apoA, apoB) were determined by use of the Hitachi 902 analyzer, and hemoglobin was determined by using ADVIA analyzer, as described previously (Kimak et al, 2010). ApoA-I and apoB were measured using the turbidimetric methods (Roche kits).…”
Section: Detections Of Lipid Lipoprotein and Hdl Particle Concentramentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress and inflammation have recently gained a considerable support as factors relevant in CVD in the setting of CKD. These disturbances result from overproduction, as well as impairment in the clearance of apolipoproteinB (apoB)-containing lipoproteins that reflects abnormalities in lipid substrates, enzymes, lipid transfer proteins and lipoprotein receptor activity [9][10][11][12][13][14][15][16]. Decreased HDL cholesterol has been long recognized to be a powerful negative-risk factor for CVD, and has emerged as a new target for intervention in the progression and even the regression of atherosclerosis [2].…”
Section: Discussionmentioning
confidence: 99%